Capacity building for goat livestock business "GIBRAN FARM" through utilization of livestock waste for agriculture - Suminah Suminah; Sapja Anantanyu; Emi Widiyanti; Ayu Intan Sari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The various problems farmers face in Kaliwedi Village include farmers' lack of knowledge in their farming practices, which impacts the condition of agricultural land saturated with chemicals. On the other hand, there is already a goat breeding business "GIBRAN FARM" managed by youths in Kaliwedi Village, with around 200 goats, and cattle belonging to farmers that have not been used for agriculture. The Community Partnership Program (PKM) is carried out as an effort to solve problems in the form of sheep farming management training, training on making kohe fertilizer, business management and marketing of kohe fertilizer, a demonstration plot of the application of kohe fertilizer to chili plants. Program partners are GIBRAN FARM sheep breeders and 10 millennial farmer groups. The results of this effort are increased livestock management knowledge, the availability of kohe fertilizer which has been tested and is ready to be marketed, partners carry out business management and marketing kohe fertilizer, there is a demonstration plot for applying kohe fertilizer to chili plants. It is hoped that this will increase the income of GIBRAN FARM sheep breeders and help farmers increase soil fertility, maintain plant health, reduce negative impacts on the environment, and realize sustainable agriculture.